2017
DOI: 10.1002/jobm.201600683
|View full text |Cite
|
Sign up to set email alerts
|

Prospecting fungal parasites of the potato cyst nematode Globodera pallida using a rapid screening technique

Abstract: Seven filamentous fungal species were isolated from individual eggs of Globodera pallida cysts collected from infested fields in Shelley Idaho, USA and identified as Chaetomium globosum, Fusarium oxysporum, Fusarium solani, Fusarium tricinctum, Microdochium bolleyi, Purpureocillium lilacinum, and Plectosphaerella cucumerina. Their ability to reduce infection by G. pallida in planta were assessed in simple, reproducible micro-rhizosphere chambers (micro-ROCs). All fungi reduced G. pallida infection in potato, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…B. thuringiensis produces proteinaceous protoxin crystals (called crystal protein or Cry protein) that cause lysis of the intestine and the nematode's death (Griffitts et al, 2005;Vachon et al, 2012). P. cucumerina was also isolated from the egg masses of M. incognita (Yu and Coosemans, 1998) and eggs of G. pallida (Kooliyottil et al, 2017), and has been found to infect eggs of G. rostochiensis (Atkins et al, 2003). The microbial community analysis using bacterial 16S rRNA gene and ITS amplicon sequencing from G. pallida females showed a dominance of diverse microbiota such as Burkholderia, Bosea, Rhizobium, Devosia, Ralstonia, and Streptomyces, and the fungal genera Davidiella, Hirsutella, Malassezia, Microdochium, Monographella, and Penicillium in potato monoculture soil (Eberlein et al, 2016).…”
Section: Microbes Identified In a Direct Association To Ppnmentioning
confidence: 99%
“…B. thuringiensis produces proteinaceous protoxin crystals (called crystal protein or Cry protein) that cause lysis of the intestine and the nematode's death (Griffitts et al, 2005;Vachon et al, 2012). P. cucumerina was also isolated from the egg masses of M. incognita (Yu and Coosemans, 1998) and eggs of G. pallida (Kooliyottil et al, 2017), and has been found to infect eggs of G. rostochiensis (Atkins et al, 2003). The microbial community analysis using bacterial 16S rRNA gene and ITS amplicon sequencing from G. pallida females showed a dominance of diverse microbiota such as Burkholderia, Bosea, Rhizobium, Devosia, Ralstonia, and Streptomyces, and the fungal genera Davidiella, Hirsutella, Malassezia, Microdochium, Monographella, and Penicillium in potato monoculture soil (Eberlein et al, 2016).…”
Section: Microbes Identified In a Direct Association To Ppnmentioning
confidence: 99%
“…Furthermore, P. cucumerina AR1 was described as a biological control agent against potato cyst nematodes (Atkins et al, 2003; Jacobs et al, 2003; Dandurand and Knudsen, 2016; Kooliyottil et al, 2017). It was used as a bioherbicide in agricultural crops and pastures (Bailey K. et al, 2017; Bailey K.L.…”
Section: Discussionmentioning
confidence: 99%
“…globosum is reported to be a fungal parasite which isolated from egg of Globodera pallida (cyst nematode) in USA. It showed the greatest reduction of the infection by G. pallida in potato of 76 % [29]. The endophytic Ch.…”
Section: Agricultural Inputsmentioning
confidence: 98%